Characteristics of the surface water basins of the Ukrainian Danube region toxicity with the use of microbial test-system Salmonella typhimurium ТА 98 - L. I. Kovalchuk; A. V. Моkiyenko; T. Yu. Vasiliyeva (Kazimierz Wielki University, 2015)
Коvalchuck L I, Моkiyenko А В, Vasiliyeva Т Yu. Характеристика токсичності води поверхневих водойм Українського Придунав'я з використанням мікробної  тест-системи Salmonella typhimurium ТА 98 = Characteristics of the surface water basins of the Ukrainian Danube region toxicity with the use of microbial test-system Salmonella typhimurium ТА 98. Journal of Education, Health and Sport. 2015;5(4):366-373. ISSN 2391-8306. DOI 10.5281/zenodo.17592 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A366-373 https://pbn.nauka.gov.pl/works/559829 http://dx.doi.org/10.5281/zenodo.17592 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.03.2015. Accepted: 30.04.2015.   УДК 504.45(477.74):574.64:579   ХАРАКТЕРИСТИКА токсичнОстІ ВОДИ поверхневих водойм Українського Придунав'я з використанням мікробної тест-сиСтемИ Salmonella typhimurium ТА 98 Characteristics of the SURFACE water BASINS Of THE UKRAINIAN DANUBE REGION TOXICITY WITH THE USE OF MICROBIAL TEST-SYSTEM Salmonella typhimurium ТА 98   1Л. Й. Ковальчук, 2А. В. Мокієнко, 3Т. Ю. Васильєва 1L I Коvalchuck, 2А В Моkiyenko, 3Т Yu Vasiliyeva   1Одеський національний медичний університет, м. Одесса 2Український НДІ медицини транспорту, м. Одеса 3Одеський національний університет ім. І.І. Мєчнікова, м. Одеса 1Odessa national medical university, Odessa, Ukraine 2State Enterprise Ukrainian Research Institute for Medicine of Transport of the Ministry of Health Care, Odessa, Ukraine 3I I Mechnikov Odessa National University, Odessa, Ukraine   The results of  the surface water basins of the Ukrainian Danube region  toxicity with the use of microbial test -system Salmonella typhimurium ТА 98.  The samples investigated testify about a majority of pollutants which are in the water. It has been shown that the most part of the samples under analysis had a powerful toxic effect. The percentage of the water samples with test - system toxicity equal to 90.0% was 13,3 %; with toxicity equal to 80,0 %  - 13,3 %;  with toxicity  > 50,0%  - 53,0 %; with toxicity < 20,0%  - 13,3 %. The percentage of non-toxic samples was 6,6 %. As test - system Salmonella typhimurium ТА 98 is moe sensitive to the organic pollutants we suggested that the water samples pollution is connected just with the presence of some organic compounds which have a great negative biological potential. Taking into account the persisting character of the surface water basins of the Ukrainian Danube region  pollution it was concluded that it is necessary to continue the research of these waters toxicity on bacterial test-system Salmonella typhimurium ТА 98.   Key words: water objects, test-system Salmonella typhimurium TA 98, Ukrainian Danube Region.   У роботі представлені результати досліджень токсичності води поверхневих водойм Українського Придунав'я з використанням мікробної  тест-системи Salmonella typhimurium ТА 98. Досліджені проби викликають різноманітні біологічні відгуки в модельній бактеріальній системі  Salmonella typhimurium ТА 98, що свідчить про різноманіття забруднювачів, які знаходяться у воді.  Показано, що більшість з досліджених зразків  води викликала  потужний токсичний ефект: відсоток зразків води, які викликали токсичність для тест-системи на рівні 90,0 % склав 13,3 %; на рівні 80,0 %  - 13,3 %; на рівні > 50,0%  - 53,0 %; на рівні < 20,0%  - 13,3 %. Оскільки тест-система Salmonella typhimurium ТА 98 більш чутлива до забруднювачів органічного походження, висловлено думку, що забруднення зразків води пов'язано саме з присутністю деяких органічних сполук, які мають великий негативний біологічний потенціал. Відсоток нетоксичних зразків води   складав 6,6 %. Зважаючи на персистувальний характер забруднення поверхневих водойм Українського Придунав'я, визнано необхідним продовження досліджень токсичності  води цих водних об'єктів на бактеріальній тест-системі Salmonella typhimurium ТА 98.   Ключові слова: вода, водні об'єкти, токсичність,  тест-система Salmonella typhimurium TA 98, Українське Придунав'є.   ХАРАКТЕРИСТИКА  ТОКСИЧНОСТИ ВОДЫ ПОВЕРХНОСТНЫХ ВОДОЕМОВ УКРАИНСКОГО Придунавья С ИСПОЛЬЗОВАНИЕМ МИКРОБНОЙ  ТЕСТ-СИСТЕМЫ  Salmonella typhimurium ТА 98. В работе представлены результаты исследований токсичности воды поверхностных водоемов Украинского Придунавья с использованием микробной  тест-системы Salmonella typhimurium ТА 98.